Social Cognitive Career Theory on Entrepreneurial Intention of Vocational Students: Teori Karier Kognitif Sosial terhadap Intensi Berwirausaha Siswa SMK - Ambarita, Nita; Butar Butar, Senita (Universitas Muhammadiyah Sidoarjo, 2024)
This study aims to examine the mediating role of outcome expectation and self-efficacy in the relationship between entrepreneurial knowledge and entrepreneurial intention among vocational students. Using a sample of 150 SMK students, data was collected via questionnaires and analyzed using the structural equation modeling (SEM) technique in Smart PLS 3.0, with Social Cognitive Career Theory (SCCT) as the theoretical framework. The results show that 1) entrepreneurial knowledge positively influences entrepreneurial intention, 2) self-efficacy mediates the relationship between entrepreneurial knowledge and entrepreneurial intention, and 3) outcome expectation also mediates this relationship. These findings contribute to the literature by validating SCCT in understanding entrepreneurial intention. The practical implications suggest the need for fostering an entrepreneurial ecosystem within the school environment as a strategy to increase entrepreneurial interest among vocational students.